Status and genetic diversity of captive tiger (Panthera tigris) in Vietnam - Canh, Le Xuan; Quynh, Ha Quy; Phuong, Dang Huy; Manh, Vuong Tien; Tung, Do Quang (Academia Journal of Biology, 2012)
The survey of tiger captivity (Panthera tigris) in Vietnam 2011 showed that there are 110 individuals of tiger in captivity included adult and young tigers kept in 11 farms  of those 4 famrs keep tigers for display, tourism with fee; 2 farms keep for public display, education, conservation, research and zoo; 8 farms keep for breeding; 5 farms keep for display only. There are six of ten farms satisfy the animal medical care. Processed 38 of 40 DNA samples collected  from 6 farms. Used 18 gens position to identify subspecies. Identified 3 subspecies of tiger in 6 farms included: 1. Panthera tigris altaica, 7 samples (7 individuals); 2. Panthera tigris corbetti, 25 samples (25 individuals); 3. Panthera tigris tigris, 4 samples (4 individuals).